Pemanfaatan tanaman Toga sebagai minuman kesehatan tradisional bagi perempuan di Desa Dukuhmojo - Sjafiatul Mardliyah; Yatim Riyanto; Soedjarwo Soedjarwo (Universitas Hamzanwadi, 2023)
Dukuhmojo Village, Mojoagung District, Jombang Regency, is a village where the majority of its population belongs to the lower-middle socioeconomic group, with farming as their main livelihood. Unfortunately, the community's understanding of the importance of maintaining health is still limited due to the influence of globalization, which has led to a tendency towards instant and unhealthy food consumption. Despite the abundance of family medicinal plants in the area, they are not fully utilized by the local residents, who prefer to purchase medicines from local shops. Therefore, this activity aims to accompany the community, especially the women of Dukuhmojo Village, in utilizing and processing the family medicinal plants (FMP) available in the vicinity, to create traditional herbal beverages as natural alternative remedies that can be sold as entrepreneurial products. The implementation method of the activity involves lectures, discussions, and assignments in several meetings with a group of ten women. The results of this community engagement demonstrate that the women's group in the village is capable of entrepreneurship and building self-confidence in creating a business of producing healthy beverages from medicinal plants, which they collectively named